Hemostatic efficacy and safety of the hemostatic powder UI-EWD in patients with lower gastrointestinal bleeding - Boram Cha; Donghyun Lee; Jongbeom Shin; Jin-Seok Park; Gye-suk Kwon; Hyungkil Kim (BMC Gastroenterology, 2022)
Abstract Background and aims Acute lower gastrointestinal bleeding (LGIB) is a common cause of emergency hospitalization and may require readmission for re-bleeding. Recently, a novel endoscopic hemostatic powder (UI-EWD/Nexpowder™, Nextbiomedical, Incheon, South Korea) was developed and applied for the control of LGIB. The aim of this study was to evaluate the hemostatic efficacy and long-term safety of UI-EWD in LGIB. Patients and methods We conducted a retrospective cohort study of LGIB at a single tertiary center in south Korea. One hundred and sixty-seven consecutive patients with LGIB who were initially successful in endoscopic hemostasis were included and divided into the conventional treatment group (n = 112) and the UI-EWD therapy group (n = 55; 38 patients with conventional treatment and 17 patients with UI-EWD alone). The success rate of hemostasis, adverse events related to UI-EWD, and re-bleeding rate were evaluated. Results The incidence of endoscopic hemostasis applied to the hepatic flexure (7.3% vs. 0%, p = 0.011) and larger than 4 cm (25.5% vs. 8.0%, p = 0.002) were significantly higher in the UI-EWD group than in the conventional therapy group. The cumulative rebleeding rate within 28 days in the UI-EWD group was 5.5% (3/55), which was significantly lower than that in the conventional treatment group (17.0% [19/112]; p = 0.039). No UI-EWD-related adverse events were recorded. Conclusion Based on our results, application of UI-EWD in LGIB showed promising results for the prevention of re-bleeding, especially in locations where it is difficult to approach or cases with more bleeding. There were no significant complications, such as perforation or embolism. In particular, UI-EWD should be considered first for anatomical or technical impediments to endoscopic access in LGIB.